The essentials of computer organization and architecture - Null, Linda; Lobur, Julia (Jones and Bartlett Publishers, 2005)
The Student Lecture Companion ia your partner and guide in note taking and provides you with a visual guide that follows the chapter topics presented in your textbook, The Essentials of Computer Organization and Architecture. The main topics covered in the lecturers are listed in the Table of Contents. No more skimming through chapter after chapter trying to find the term you need to understand!